EXPLORING CRITICAL PEDAGOGY PRINCIPLES IN EFL CLASSROOMS: BELIEFS AND PRACTICES OF INDONESIAN TEACHERS - Yulianto, Slamet Wahyudi; Musthafa, Bachrudin; Gustine, Gin Gin (English Review: Journal of English Education, 2024)
The incorporation of critical pedagogy (CP) principles in the teaching of English as a foreign language (TEFL) in Indonesia has been promoted since the last two decades. However, research on how Indonesian EFL teachers view the CP principles are rarely conducted. This case study aims to discover the perceptions of 30 Indonesian EFL teachers teaching in different levels of education and having various educational backgrounds and diverse degree of familiarity regarding the four CP principles. The data for this study were collected by distributing questionnaires and conducting interviews. The collected data were analyzed using descriptive analysis and by transcribing, tabulating, coding, categorizing, interpreting, comparing, and concluding. It is evident from the participants’ viewpoints, among the four principles, dialogue and problem-posing are the two most desirable as well as applicable ones. Additionally, in practicing the four principles, the participants claimed that they performed twelve categories of classroom activities. Considering the findings of this study, more training and research on critical EFL pedagogy are recommended.